LOVE OBSESSION IN GASTON LEROUX’S THE PHANTOM OF THE OPERA - Meica Angellia; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2017)
This research was aimed to find out the way Erik conducts his love obsession towards Christine Daae in The Phantom of The Opera, and to find out the effects of Erik’s love obsession toward himself and Christine Daae’s life. This research was descriptive. The data of this research were words, phrases, clauses, paragraphs, or discourses containing love obsession in the novel The Phantom of The Opera written by Gaston Leroux. The source of data was document, namely a novel entitled The Phantom of The Opera. The technique of collecting the data was document analysis. Moreover, sociological approach and psychological approach were applied to decide the strategy in analyzing the love obsession and the effect found in the novel. The analysis shows that: (1) the way Erik conducts his love obsession by ruling Christine Daae and trying to do anything to get Christine Daae. Furthermore, (2) the effect towards Christine’s life is she is being oppressed and the effect toward Erik is he is become depressed. The conclusion is people who suffer from love obsession can do negative things such as, manipulating, sabotaging, threatening, setting a trap and kidnapping. The effects can be bad such as, being oppressed for the object of love obsession and getting depressed for the person suffering from love obsession. Keywords: Love Obsession, Obsession, Psychology